P0336INHIBITION C-C CHEMOKINE RECEPTOR TYPE 2 (CCR2) ON ACTIVATED KIDNEY PARIETAL EPITHELIAL CELLS REVEALS A NEW THERAPEUTIC APPROACH FOR CHRONIC KIDNEY DISEASES. (6th June 2020) - Zhao, Bin; Miao, Zhenhua; Campbell, James; Ertl, Linda S; Wang, Yu; Li, Chris; Singh, Rajinder; Charo, Israel F; Schall, Thomas J
Abstract: Background and Aims: We have recently demonstrated that small molecule inhibitors of CCR2 rapidly reduced proteinuria and preserved renal structure in animal models of diabetic nephropathy (DN) and focal segmental glomerular sclerosis (FSGS). Similar beneficial effects of CCR2 inhibition were also observed in DN patients in a large diabetic nephropathy Phase 2 clinical trial. Despite its rapid and robust effects in these kidney diseases, the mechanism by which CCR2 inhibition affords such renal protection remains unclear. CCR2 is well-known to be expressed on cells of the immune system, where it mediates inflammation and immunological functions by controlling the trafficking of monocytes and T cells. However, immune cell expression of CCR2 may not adequately explain the rapid pharmacologic benefits of CCR2 inhibitors in DN and FSGS because these diseases do not exhibit appreciable kidney inflammation. To better understand the protective mechanism(s) of CCR2 inhibition in renal diseases, we have used a variety of in vivo nephropathy models to determine if CCR2 is expressed on kidney parenchymal cells. Our results suggest that a subset of CD45 negative, renal parietal epithelial cells express CCR2. Method: To characterize CCR2 expression in the kidney we used CCR2 RFP heterozygous mice (CCR2 RFP/+ ) in which one copy of CCR2 was replaced by red fluorescent protein (RFP), whose expression is under the control of the endogenous CCR2 promoter. This approach provided a highly sensitive method for CCR2 detection by both flow cytometry and immunofluorescence, and compensated for the lack of validated, commercially available anti-CCR2 antibodies. Enriched glomerular cells were obtained by a non-enzymatic disruption of kidneys, followed by centrifugation at low speed (80gs), and sieving through 300µm and 150µm meshes. The Adriamycin (ADR)-nephropathy model with CCR2 RFP heterozygous mice was used to determine CCR2 expression on renal cells. 5/6 nephrectomy models of FSGS, as well as the db/db diabetic nephropathy model were used to access the change of activated parietal epithelial cells and proteinuria, both in the presence and absence of a CCR2 inhibitor in the setting of kidney injury. Results: We observed dramatic increases in the number of activated parietal epithelial cells (PECs, identified as CD133 + CD24 + CD44 hi cells by flow cytometry) in all three renal disease models. In the ADR nephropathy model, we found that in 30-40% of activated PEC cells within an enriched population of glomerular cells expressed CCR2/RFP. CD44 hi RFP + increased much more dramatically than CD44 hi RFP - cells in response to ADR, and this was highly correlated with proteinuria, suggesting that CCR2 plays an important role in PEC cell activation and kidney pathology in ADR induced kidney injury. Furthermore, we found that blocking CCR2 with the CCR2-specific antagonist CCX872 significantly reduced both proteinuria and the number of activated PECs in the 5/6 nephropathy and db/db diabetic nephropathy models. Conclusion: This is the first report that CCR2 is present on a subset of activated renal PECs. This population is markedly upregulated during kidney injury in a variety of murine models of nephropathy. Changes in the abundance CCR2+ activated PECs in the glomerular enriched preparations in response to CCR2 inhibition suggests that CCR2 antagonism may represent a novel approach for the treatment of chronic kidney disease.